Investigation of the Exhaust Gas Emissions from Light Vehicles in the Technical Examination Centers in 2016 (Case Study: Hamadan City) - Mostafa Leili; Mehdi Salari; Azam Nadali (Muhandisī-i Bihdāsht-i Muḥīṭ, 2017)
Background: Expanding urbanization and increasing the number of vehicles have led to adverse effects on both the environment and human health. The propose of this study is to evaluate the concentration of CO2, CO, HC, O2, NOX in the exhaust outlet of vehicles tested in technical examination center, and to determine the relationships between their variation and lambda coefficient, type of fuel injection system as well as vehicle type. Methods: This cross-sectional study was conducted on 1000 vehicles tested in technical examination centers in Hamadan city. To do this, the concentrations of CO2, CO, HC, O2, NOX gases emission were obtained, and then the relations between variation of these gases and lambda coefficient, type of fuel injection system and vehicle type were investigated. The statistical analysis that used in this study include one-way ANOVA and independent t-test (SPSS 16). Results: The results of this study showed a significant relationship between the concentration of emitted gases and the lambda coefficient, the vehicle type and the type of fuel injection system (p<0.05). The lambda coefficient equal to 1 was recognized as the best combustion condition because the availability of sufficient oxygen for the reactions lead to reduction of CO and HC emissions. The fuel injection system had a significant effect on reducing the emissions due to the suitable distribution of fuel and increasing combustion efficiency. Conclusion: In the current study, it was observed that personal vehicles due to lower depreciations than the taxis, and the injector systems due to better distribution of the fuel than the carburetor ones, have better conditions in term of pollutants emissions.